ANALISIS PENGARUH ANTARA DISIPLIN KERJA, KOMPENSASI, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN PT SEJATI KARYA PERKASA MEDAN - Kosasih, Hengky (UNIKA Santo Thomas, 2021)
This research is motivated by the level of work discipline, compensation and organizational structure at PT Sejati Karya Perkasa Medan which is still not good. This can be seen from the increase in employee absenteeism and delays as well as employee absenteeism every year so that it has an impact on decreasing employee performance. This study is a descriptive study with a quantitative approach, with a population of 87 employees and taking a sample of 87 people using the census method, then analyzed with multiple regression analysis with the results showing that there is a positive and significant influence between work discipline, compensation and organizational culture on employee performance. Based on the termination test of 65.9%, while the most influential variable is work discipline.